Co-Amoxiclav Induced Immune Haemolytic Anaemia: A Case Report - H. G. C. S. Karunathilaka; D. P. Chandrasiri; P. Ranasinghe; V. Ratnamalala; A. H. N. Fernando (Case Reports in Hematology)
Drug-induced immune haemolytic anaemia (DIIHA) is extremely rare. We herein report a case of DIIHA due to co-amoxiclav. A 53-year-old male being treated for left-sided pyelonephritis with intravenous co-amoxiclav developed symptoms and signs of anaemia on the third day of treatment. He was found to have evidence of haemolysis with a positive Coombs test and IgG antibodies and C3d. Co-amoxiclav was identified as the probable culprit, using the Naranjo adverse drug reaction probability scale. Upon discontinuation of the drug and blood transfusion, the patient’s haematological parameters stabilised. Steroids were not required in the treatment. Diagnosis of DIIHA is made through a history of intake of co-amoxiclav, clinical and laboratory features of haemolysis, and a positive Coombs test. An autoantibody screen is most commonly negative. It is essential for clinicians to be aware about this rare complication caused by commonly prescribed drugs and be able to accurately diagnose and initiate treatment.